THE EFFECT OF DIFFERENT DOSES OF rGH ON GROWTH RATE OF RIVER CATFISH (Mystus nigriceps) IN RECIRCULATION AQUACULTURE SYSTEM - Miliani, Ririn; Tang, Usman Muhammad; Pamukas, Niken Ayu (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
ABSTRACTThe research aims to determine the the best doses of recombinant growth hormone (rGH) in commercial feed on the growth rate of Mystus nigriceps in culture of resirculation system. The experiment was conducted from 25 July to 24 August 2018 at Laboratorium Cultivation Technology Faculty of The Fisheries of Marine, University of Riau. This research used experimental method use was completely randomized design (CRD) with of 5 treatments and 3 replicates. Wich were treatments 0, 2, 4, 6 and 8 mg/1000g of commercial feed PF 800. Fish samples used are the catfishes  with an average length of 4-5 cm and weight of 0,3-0,6 g are readed in aquarium (40x30x30) cm3 in a density 2 individu/L. The fish were fed with the rGH supplemented diet one three days 5% body weight. The results showed that fish treatment by rGH with doses of 2 mg/1000g feed was the best treatment than other treatment with value of growth body weight (5,15 g) and lenght (5,52 cm), specific growth rate (9,47 %), feed efficiency (83,05%) and feed convertion (1,21) of fish. That conclution is giving rGH significantly affect the growth rate  and the best doses are 2 mg/1000g feed. Keywords:Mystus nigriceps, recombinant growth hormone, resirculation system